Late Presentation With HIV in Africa: Phenotypes, Risk, and Risk Stratification in the REALITY Trial. (4th March 2018) - Siika, Abraham; McCabe, Leanne; Bwakura-Dangarembizi, Mutsa; Kityo, Cissy; Mallewa, Jane; Berkley, Jay; Maitland, Kath; Griffiths, Anna; Baleeta, Keith; Mudzingwa, Shepherd; Abach, James; Nathoo, Kusum; et al.
Abstract: Background: Severely immunocompromised human immunodeficiency virus (HIV)–infected individuals have high mortality shortly after starting antiretroviral therapy (ART). We investigated predictors of early mortality and "late presenter" phenotypes. Methods: The Reduction of EArly MortaLITY (REALITY) trial enrolled ART-naive adults and children ≥5 years of age with CD4 counts <100 cells/µL initiating ART in Uganda, Zimbabwe, Malawi, and Kenya. Baseline predictors of mortality through 48 weeks were identified using Cox regression with backwards elimination (exit P > .1). Results: Among 1711 included participants, 203 (12%) died. Mortality was independently higher with older age; lower CD4 count, albumin, hemoglobin, and grip strength; presence of World Health Organization stage 3/4 weight loss, fever, or vomiting; and problems with mobility or self-care at baseline (all P < .04). Receiving enhanced antimicrobial prophylaxis independently reduced mortality ( P = .02). Of five late-presenter phenotypes, Group 1 (n = 355) had highest mortality (25%; median CD4 count, 28 cells/µL), with high symptom burden, weight loss, poor mobility, and low albumin and hemoglobin. Group 2 (n = 394; 11% mortality; 43 cells/µL) also had weight loss, with high white cell, platelet, and neutrophil counts suggesting underlying inflammation/infection. Group 3 (n = 218; 10% mortality) had low CD4 counts (27 cells/µL), but low symptom burden and maintained fat mass. The remaining groups had 4%–6% mortality. Conclusions: Clinical and laboratory features identified groups with highest mortality following ART initiation. A screening tool could identify patients with low CD4 counts for prioritizing same-day ART initiation, enhanced prophylaxis, and intensive follow-up. Clinical Trials Registration: ISRCTN43622374.